High serum level of soluble CD30 in acute primary HIV-1 infection - PIZZOLO, G (Blackwell Science Inc, 1997)
CD30 has been suggested to play a role in HIV infection. In this study the serum concentration of soluble CD30 (sCD30) was determined by an ELISA essay on samples collected from patients with acute primary HIV-1 infection during the acute phase (n = 17) and after seroconversion (n = 13). sCD30 during acute infection was consistently elevated (137.58 ± 120.33 versus 6.4 ± 5.4 U/ml (mean ± s.d.) in normal controls; P < 0.0001) and decreased after seroconversion (49.1 ± 66.17 U/ml; P = 0.0018 compared with acute infection). This trend mirrored the disappearance of detectable levels of HIV antigen in the blood, resulting in a direct correlation between sCD30 and HIVAg values (P = 0.002). These data suggest that the high levels of sCD30 observed during the peak concentration of HIVAg in acute primary HIV infection might reflect the high rate of viral replication.